Grammatici Latini - Keil, Heinrich, (Cambridge library collection. Linguistics)
The eight volumes of the Grammatici Latini, published by Teubner between 1855 and 1880 under the general editorship of Heinrich Keil (1822-1894), are an outstanding monument of nineteenth-century German philology. Keil published editions of Propertius and of Pliny's letters before turning to the works of the Latin grammarians, whose attempts to define and describe their own language have influenced the way in which modern researchers in language and linguistics have approached their discipline. Keil's only predecessor in this field was Helias Putsch, who in 1605 published Grammaticae Latinae auctores antiqui; Keil uses the same order in which to present his versions of the texts. The first volume contains the work of Charisius and Diomedes. v. 1. Flavii Sosipatri Charisii Artis Grammaticae Libri V, Diomedis Artis Grammaticae Libri III, ex Charisii Arte Grammatica excerpta -- v. 2. Prisciani Institutionum Grammaticarum Libri I–XII -- v. 3. Prisciani Institutionum Grammaticarum Libri XIII–XVIII, Prisciani opera minora -- v. 4. Probi, Donati, Servii qui feruntur de arte grammatica libri, et Notarum laterculi -- v. 5. Artium scriptores minores -- v. 6. Scriptores artis metricae -- v. 8. Anecdota Helvetica quae ad grammaticam Latinam spectant.